Ocupação das áreas de risco à erosão na área urbana e periurbana de Cidade Gaúcha - Paraná - Macedo, Felipe Rodrigues (2015)
During the 1990s was conducted geotechnical mapping of five cities in the Northwest of the Paraná State in an agreement between the Maringá State University, Geography Department and the Supervision of Erosion Cidade Gaúcha in this work analyses past 20 years, the main points of the original mapping, in order to ascertain whether the work was actually applied in urban and peri-urban areas. This research also, verifies use the mapping against the National Policy of Protection and Civil Defence (PNPDEC). It were not observed erosion problems in the rural areas with pastures that still support the recommendations of Paraná Rural Programme, already in the rural areas with sugarcane, sheet erosions were found. In the case of Cidade Gaúcha, the major erosional features are found in the urban area. Three areas have been identified, at the time, as problematic, in the urban area, and in two of them still have problems and the other place is in better conditions, without presenting erosional features. In the first of these, the erosive feature is around 23 metres of houses, with source presence. The second is occurring the reactivation of an erosive feature, because the works carried out for the erosive control had not produced the desired results. Already the third sector presented better conserved, influenced by an Area of Interest to the Protection (ZIP) creation and with low occupation of nearby streets, which assisted in rainwater infiltration. In terms of PNPDEC, the mapping carried out in 1994, was of great quality, not only in marking of zones, but also in the occupation guidelines. All the problems of erosion found now were caused probably by the lack of application of the original geotechnical mapping.